Development of PCS to utilize differential pressure energy in district heating systems with reduced DC-link voltage variation - Bak, Yeongsu; Lee, Kyo Beum (Journal of Power Electronics, 2020)
This paper proposes a power conversion system (PCS) to utilize the differential pressure (DP) energy in district heating systems with reduced DC-link voltage variation. A differential pressure control valve (DPCV) is usually used to regulate pressure for heat transmission to remote areas in district heating systems. However, there is a high probability of malfunctions and failures of the DPCV, due to cavitation, since high-pressure fluids are used in district heating systems. Therefore, a PCS for utilizing DP energy in the district heating system replacing the DPCV is proposed in this paper. In addition, the DC-link voltage of the PCS greatly fluctuates when a sudden change occurs in a hydraulic turbine. It is effectively relieved by using the feed-forward control method. The effectiveness of the PCS for utilizing the DP energy in district heating systems with reduced DC-link voltage variation is verified by simulation and experimental results.
Keywords: DC-link voltages; Differential pressures; District heating system; Heat transmission; High probability; High-pressure fluids; Power conversion systems; Sudden change; Back-to-back converter; DC-link voltage variation; Differential pressure control valve; District heating system; Permanent-magnet synchronous generator